Inclusive Islamic Education Management: Strengthening Religious Moderation in Schools - Moh. Kholip Beril arrahman; Siti Aimah (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat (LP3M) IAI Al Urwatul Wutsqo - Jombang, 2026)
This study aims to analyze the strategy of inclusive Islamic education management in strengthening religious moderation in high schools in Banyuwangi Regency. Using a case study design, this study dissects the orchestration of the five pillars of management: curriculum, leadership, teacher competence, student engagement, and digital mitigation. The findings show that the transformative leadership of school principals is a determinant pillar or